Islamic Ecotheological Orientation: Hifdz al-Bi'ah as an Effort to Maintain Ecosystem Balance - Moh. Alfin Sulihkhodin; Hikmal Ramadhan; Muhammad Asadurrohman; Nova Fransisca Lauziningrum; Dhivio Bintang Yudho Purnomo (Santara: Journal of Islamic Law and Humanity, 2026)
This study is motivated by the increasing severity of environmental degradation and natural disasters in Indonesia and globally, which reflect an imbalance in the relationship between humans and nature. Such conditions indicate not only ecological crises but also ethical and spiritual disorientation in human behavior toward the environment. In this context, Islamic eco-theology offers a normative framework rooted in the Qur’an, Hadith, and the principles of maqāṣid al-sharī‘ah, particularly the concept of hifẓ al-bi’ah. Therefore, this research aims to examine the orientation of Islamic eco-theology and to analyze how hifẓ al-bi’ah functions as a conceptual and ethical foundation in maintaining ecosystem balance and addressing global environmental challenges. This research employs a qualitative approach through library research, utilizing a descriptive-analytical method. Data were collected from primary Islamic sources, including the Qur’an and Hadith, as well as relevant scholarly literature on eco-theology and maqāṣid al-sharī‘ah. The analysis focuses on interpreting Islamic teachings related to environmental ethics and exploring their relevance within contemporary ecological issues. The findings reveal that Islamic eco-theology positions environmental preservation as an integral obligation of humans as khalīfah (stewards) on earth. The concept of hifẓ al-bi’ah emerges as a significant extension of maqāṣid al-sharī‘ah, emphasizing the necessity of maintaining ecological balance, preventing environmental destruction, and avoiding excessive exploitation of natural resources. The originality of this study lies in its integrative approach, which frames hifẓ al-bi’ah not merely as a normative principle, but as an operational and contextual paradigm that connects theological, ethical, and ecological dimensions in responding to the contemporary environmental crisis.